2016
DOI: 10.1111/acer.12938
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Effects of Ethanol and/or Darunavir/Ritonavir on U937 Monocytic Cells: Regulation of Cytochrome P450 and Antioxidant Enzymes, Oxidative Stress, and Cytotoxicity

Abstract: Background Our recent study has shown that acute treatment with ethanol increases oxidative stress and cytotoxicity through cytochrome P450 2E1 (CYP2E1)-mediated pathway in U937 monocytic cells. U937 cells are derived from blood monocytes and are considered as the model system for HIV-related study. Since the prevalence of alcohol use in HIV-infected population is high, and HIV+ patients are on antiretroviral therapy (ART) soon after they are diagnosed, it is important to study the interactions between ethanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 54 publications
2
19
0
Order By: Relevance
“…Fifth, even direct ex vivo incubation of leukocytes with ritonavir, at concentrations similar to maximum one hour post-treatment plasma levels, only weakly impacted oxidative responses and had little to no effect on phagocytosis 47 . Sixth, direct in vitro incubation of monocytic cells with 1 μM ritonavir for 4 days did not reduce superoxide production and did not alter proliferative responses 48 . Finally, even if ritonavir therapy does alter some aspect of leukocyte infiltration or function that we have not assessed, the mice are still protected from hippocampal injury and seizures without jeopardizing viral clearance or health of the host, supporting our contention that ritonavir treatment may be a unique neuroprotective intervention during acute viral encephalitis 41 .…”
Section: Discussionmentioning
confidence: 93%
“…Fifth, even direct ex vivo incubation of leukocytes with ritonavir, at concentrations similar to maximum one hour post-treatment plasma levels, only weakly impacted oxidative responses and had little to no effect on phagocytosis 47 . Sixth, direct in vitro incubation of monocytic cells with 1 μM ritonavir for 4 days did not reduce superoxide production and did not alter proliferative responses 48 . Finally, even if ritonavir therapy does alter some aspect of leukocyte infiltration or function that we have not assessed, the mice are still protected from hippocampal injury and seizures without jeopardizing viral clearance or health of the host, supporting our contention that ritonavir treatment may be a unique neuroprotective intervention during acute viral encephalitis 41 .…”
Section: Discussionmentioning
confidence: 93%
“…Ethanol treatment exhibited a significant decrease in the apparent half-life (t 1/2 ) for DRV + RTV (Fig. 2A, (F (3,11) = 34, P = 0.003, one-way ANOVA) but not for the DRV alone ( P = 1). We observed increased trend in K value for DRV + RTV when exposed to ethanol but this increase is not statistically significant (F (3,11) = 88, P = 0.151, one-way ANOVA) when compared to DRV + RTV condition.…”
Section: Resultsmentioning
confidence: 94%
“…5). Ethanol induced HIV replication in monocytes cells appears to be via CYP2E1-mediated alcohol metabolism and resultant oxidative stress (7,11,23). Similar to 20 mM ethanol concentration, ethanol-induced increase in HIV replication was completely abolished when cells were treated with DRV or DRV + RTV at both 10 mM and 50 mM ethanol concentrations ( p < 0.05 compared to control or ethanol, student t test).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, another commonly used ARV, elvitegravir (EVG), is metabolized by CYP3A4 and a strong CYP3A4 inhibitor such as cobicistat (COBI) is coadministered as a booster to increase EVG bioavailability. Recently, Kumar group showed that the ethanol exposure decreases the intracellular levels of EVG alone and also in combination with COBI in HIV-infected macrophages [19,20]. Subsequently, co-exposing cells to EVG or EVG + COBI along with ethanol showed increased viral replication by 31% and 19%, respectively, relative to control groups that did not receive ethanol [19].…”
Section: Effect Of Alcohol On Cyp3a4-pi and Cyp3a4-integrase Strand Tmentioning
confidence: 99%